Assymetric effect of fiscal and monetary policies on the stock market performance in Nigeria - Adeleke, Oluwayemisi; Oyeleke, Olusola (Advances in Social Sciences Research Journal, 2021)
This study investigated the asymmetric effect of fiscal and monetary policies on stock market performance from 2000:q1-2018q3 in Nigeria. The study used Auto Regressive Distributed Lag (ARDL) Bounds Test technique of cointegration to determine the equilibrium relationship among the series. After the long run relationship has been established, Vector Error Correction Model was used to analyse the data. The results showed that only anticipated fiscal policy had a negative and significant effect on the stock market performance in the third and fourth quarters of the year. In contrast, anticipated and unanticipated monetary policy as well as unanticipated fiscal policy did not exert effect on stock market performance in Nigeria. Government in Nigeria should reduce its expenditure which has the capacity to negatively influence the performance of stock market in Nigeria.